The influences of Malaysian animated Public Service Announcements (PSAs) on public health and safety campaign and its effectiveness among students / Dzaa Imma Abd Latiff, Mohd Amirul Akhbar Mohd Zulkifli and Siti Nur Farah Faadiah Abd Ghani - Abd Latiff, Dzaa Imma; Mohd Zulkifli, Mohd Amirul Akhbar; Abd Ghani, Siti Nur Farah Faadiah (Research Management Institute (RMI), 2013)
Public Service Announcements (PSAs) are free announcements made to promote programs, activities, community interest and services from government and the non - government sector. As technology develops, many PSAs use animated characters in order to persuade and create high awareness among people. Animation is a simulation of movement created by displaying a series of pictures or frames such as cartoons on television. Research has shown that PSAs is effective in conveying the message. However, the influences of animated PSAs among students about health and safety messages are still unclear. Previous researchers were more interested to investigate the effects of PSAs to children and less research on animated PSAs towards adults. Therefore, the researcher is interested to study whether or not the animation should be utilized as an effective tool to educate the public. A sample of 285 students watched four animated PSAs and four live action PSAs. Two of each represented animated spoke characters and non spoke characters with a goal to evaluate students responses on positive attitudes. A correlation analysis was used to study the relationship between the positive response of animated PSAs and engagement with results that indicated moderate and high correlation. T tests were used to investigate the comparison between the students responses to animated PSAs versus non animated PSAs and animated spoke characters versus animated non spoke characters. The results emphasize that animated PSAs received better responses among students. Students acceptance towards animated PSAs and animated spoke characters received small but significantly better response.